FAKTOR PENENTU EKSPOR MINYAK KELAPA SAWIT DI INDONESIA - Hermien Triyowati; Julmina Nur Sabrina (Media Ekonomi, 2020)
Indonesia is a country that is abundant in natural resources both in agriculture and plantations. One of the advantages of plantation commodities owned by Indonesia is palm oil, but palm oil has experienced a decline in world demand for several years due to several factors. This study aims to analyze the determinants of palm oil exports in Indonesia. This study uses a simple regression analysis with the help of Eviews 9 analysis tools. The data used in this study are secondary data on the volume of Indonesian palm oil exports, inflation, interest rates, trade openness, exchange rate of volatility, exchange rates of Indonesian palm oil prices, the price of Malaysian palm oil, and export duties for the period of 2005 to 2019. The results can show that the determinants of palm oil exports are the price of Malaysian state palm oil and the price of Indonesian palm oil (fitted). While the exchange rate (fitted) and export duty does not affect the volume of Indonesian palm oil exports. In addition, the variable price of Indonesian palm oil is a mediating variable, while the exchange rate variable is a moderating variable.